Translatability scoring in prospective and retrospective COVID drug development cases: research - Wendler, Alexandra; Wehling, Martin (European journal of clinical pharmacology, 2023)
The ongoing pandemic of severe acute respiratory syndrome coronavirus 2 has led to an enormous surge of clinical research. So far, the speed and success rate of related drug development projects, especially of vaccines, is unprecedented. For the first time, this situation allowed for the opportunistic evaluation of a translatability score, originally proposed in 2009, in a prospective manner.